2019
DOI: 10.1088/1361-648x/ab21ee
|View full text |Cite
|
Sign up to set email alerts
|

An evidence of local structural disorder across spin-reorientation transition in DyFeO3: an extended x-ray absorption fine structure (EXAFS) study

Abstract: The present work is aimed at exploring the local atomic structure modifications related to the spin reorientation transition (SRT) in DyFeO 3 orthoferrite exploiting x-ray absorption fine structure (XAFS) spectroscopy. For this purpose we studied by XAFS the evolution of the local atomic structure around Fe and Dy as function of temperature (10-300 K) in a DyFeO 3 sample having the SRT around 50-100 K. For sake of comparison we studied a YFeO 3 sample having no SRT. The analysis of the extended region has reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…DyFeO 3 orthoferrite has the same orthorhombic crystal structure (Pbnm) of PrNiO 3 under room conditions. 31 This orthoferrite is a magnetic system with a spin reorientation transition (SRT) in the range of 50-100 K. Panchwanee et al reported a slight compression of the bond Fe-O above SRT and an anomaly in s G 2 similar to that seen for the bond Ni-O in PrNiO 3 at magnetic ordering temperature T N E 130 K, the anomaly being absent in the paramagnetic YFeO 3 orthoferrite.…”
Section: Spin-phonon Coupling Contributions In Monoclinic Prniomentioning
confidence: 95%
See 1 more Smart Citation
“…DyFeO 3 orthoferrite has the same orthorhombic crystal structure (Pbnm) of PrNiO 3 under room conditions. 31 This orthoferrite is a magnetic system with a spin reorientation transition (SRT) in the range of 50-100 K. Panchwanee et al reported a slight compression of the bond Fe-O above SRT and an anomaly in s G 2 similar to that seen for the bond Ni-O in PrNiO 3 at magnetic ordering temperature T N E 130 K, the anomaly being absent in the paramagnetic YFeO 3 orthoferrite.…”
Section: Spin-phonon Coupling Contributions In Monoclinic Prniomentioning
confidence: 95%
“…DyFeO3 orthoferrite has the same orthorhombic crystal structure (𝑃𝑏𝑛𝑚) of PrNiO3 at room conditions. 31 This orthoferrite is a magnetic system with a spin reorientation transition (SRT) in the range 50-100 K. Panchwanee et. al.…”
Section: Spin-phonon Coupling Contributions In Monoclinic Prnio3mentioning
confidence: 99%
“…The first nearest-neighbor shells around Fe and Ni both show a suppression of the bond thermal expansion, although the anharmonicity, with important quantum effects at low temperature, is clearly evident. Panchwanee et al [128] explored the local modifications associated with the spin-reorientation transition in DyFeO 3 orthoferrite. They observed a shrinkage of the Fe-O bond length above the spin-reorientation transition and the activation of static distortion of Fe-O bonds below.…”
Section: Other Applicationsmentioning
confidence: 99%